Past and present of the field of informatics at “Babeș-Bolyai” University and other institutions in Cluj-Napoca - MOLDOVAN, Grigor (Studia Universitatis Babeș-Bolyai Digitalia, 2017)
This article is centered on the story of the pioneering endeavors in the field of informatics in Romania and more specifically in Cluj-Napoca. Stemming from personal experience and reverence towards the very first professors and specialists that opened up this vast and formidable domain, this article which reads as a history of Romanian informatics, has the added benefit of filling in a noticeable gap in texts that take into account this interesting subject. Spanning from the 50s and all the way up to the 90s and tracing the opening, and transformations, and eventual closure of research centers, laboratories, and various institutional collaborations, this article brigs a better understanding of the efforts and challenges that are always seem to be intertwined with progress, but which were eventually overcome through the persistence of brilliant scholars, and sometimes even the occasional favorable policy. Special attention is given to the entity of the Calculus Centre at Babeș-Bolyai University, founded in 1975, as the author himself was its director for 17 years until it was dismantled in 1992. This too however did not mark and end, but rather a new beginning, a different model of institution that was meant to tackle the ever-changing issues informatics face today.